1982
DOI: 10.1029/ja087ia02p00853
|View full text |Cite
|
Sign up to set email alerts
|

A simple kinetic theory calculation of terrestrial atomic hydrogen escape fluxes induced by charge exchange collisions

Abstract: A simple kinetic theory model is presented for the calculation of atomic hydrogen escape fluxes from earth induced by charge exchange collisions with hot protons. An analytical expression is derived for the nonthermal flux in terms of atmospheric and dynamical variables. The results, which indicate an increase in the nonthermal flux with decreasing exospheric temperature, are in good agreement with the earlier estimates by Bertaux (1975).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
3
18
2
Order By: Relevance
“…As Tu+ increases, more collisions result in neutral hydrogen with escape velocity. This intuitive conclusion has been substantiated by an analytic expression for the escape flux, which was developed by Shizgal and Lindenfeld [ 1982].…”
Section: H+ +O--h +O + (5)mentioning
confidence: 97%
See 1 more Smart Citation
“…As Tu+ increases, more collisions result in neutral hydrogen with escape velocity. This intuitive conclusion has been substantiated by an analytic expression for the escape flux, which was developed by Shizgal and Lindenfeld [ 1982].…”
Section: H+ +O--h +O + (5)mentioning
confidence: 97%
“…These symmetric profiles provide good estimates of the critical level temperature Tc [Atreya, 1973;Atreya et al, 1975;Kerr et al, 1984]. T½is used in the parameterization of the thermal escape flux Fj, and the charge exchange escape flux FcE [Shizgal and Lindenfeld, 1982].…”
Section: Exospheric Temperaturementioning
confidence: 99%
“…Charge exchange has been studied as a principal source of non-thermal escape of H atoms at the Earth (Shizgal and Arkos 1996), Venus (Hodges 1993) and Mars (Nagy et al 1990) leading to the high D/H ratio measured in Venus' atmosphere (Donahue et al 1982). Charge exchange production of ENAs is usually considered as a nearly resonant collision, equivalent to the exchange of an electron without significant momentum transfer (Shizgal and Lindenfeld 1982;Shizgal and Arkos 1996). Kallio et al (1997) showed that at Mars the region where ENAs are formed by charge exchange between solar wind H + and exospheric O occurs on the dayside in a thin layer whose size depends on solar activity.…”
Section: Plasma-induced Escapementioning
confidence: 99%
“…Solutions have been developed for a linearized Boltzmann equation in order to describe gas flow in the transition region (Shizgal and Lindenfeld 1982;Shizgal and Blackmore 1986;Shizgal and Arkos 1996;Shizgal 1999). This approximation is used to describe the flow of hot or minor species through the background atmosphere assuming their effect is negligible .…”
Section: Boltzmann Transportmentioning
confidence: 99%
“…These nonthermal escape mechanisms play an important role in the evolution of the atmospheres of these planets [ Shizgal and Arkos , 1996]. The charge exchange process of energetic H + or D + in collision with neutral H can produce a significant population of H and D atoms with energies well above thermal [ Chamberlain , 1977; Shizgal and Lindenfeld , 1982; Hodges and Breig , 1993; Hartle et al , 1996]. The dissociative recombination of O 2 + can produce energetic oxygen atoms on all three terrestrial planets and substantial coronae of hot oxygen exist on Earth, Mars and Venus [ Nagy and Cravens , 1988; Ip , 1988].…”
Section: Introductionmentioning
confidence: 99%